Social imaginaries of childhood and its effects in the pedagogical practice of a school in Bogotá - Triviño Roncancio, Ana Virginia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article presents some theoretical and methodological advances, as well as some findings around the childhood category belonging to the research work entitled "The social imaginaries of childhood, boy, girl, and young people and the pedagogical practice in the Capital District´s school ", which was carried out at the Santa Librada IED school. The starting question of the research is about the social imaginaries of boys, girls and young people that underlie the pedagogical practice of the school teachers in Bogotá, and whether it is possible to identify their modification from an institutional pedagogical proposal. The study belongs to the field of social imaginaries and pedagogical practices, it establishes a connection between the history of the subjects, their discourse, and their practices, based on that magma of meanings that teachers build up around childhood. The school is assumed as a social space where countless senses and meanings model the ways of educating children in the coexistence of past, present, and future. Taking into account that social imaginaries are elaborations produced and unveiled in and by language, the methodology of this study is located in interpretive approaches. Research techniques such as interviews, stories, and observation were used to collect information that would allow us to reveal the imaginaries of teachers about children and their effect on the meaning of their pedagogical practice.